Regulation of hepcidin expression at high altitude. - Talbot, N; Lakhal, S; Smith, T; Privat, C; Nickol, A; Rivera-Ch, M; León-Velarde, F; Dorrington, K; Mole, D; Robbins, P (2012)
Enhanced erythropoietic drive and iron deficiency both influence iron homeostasis through the suppression of the iron regulatory hormone hepcidin. Hypoxia also suppresses hepcidin through a mechanism that is unknown. We measured iron indices and plasma hepcidin levels in healthy volunteers during a 7-day sojourn to high altitude (4340 m above sea level), with and without prior intravenous iron loading. Without prior iron loading, a rapid reduction in plasma hepcidin was observed that was almost complete by the second day at altitude. This occurred before any index of iron availability had changed. Prior iron loading delayed the decrease in hepcidin until after the transferrin saturation, but not the ferritin concentration, had normalized. We conclude that hepcidin suppression by the hypoxia of high altitude is not driven by a reduction in iron stores.